Project and change management success factors from Malaysian government departments and agencies perspective - Ghanim, Alyaa; Munassar, Fatima; Ahmad Dahlan, Abdul Rahman (International Organisation of Scientific Research (IOSR), 2013)
A project is considered as a core element in any organization and its continuity can be guaranteed through a successful change management. Confronting merciless challenges at the current time particularly at the market field, the emergency need has been raised to overcome those obstacles and step ahead on rivals. One way that most organizations have moved towards its capabilities and put the pressure on it to produce quality and optimal outcomes is ICT. Thus, various types of IT projects with variant intended objectives have been conducted. As being witnessed recently and noticed previously, that a lot of IT projects turned to fail due to several reasons. Additionally, way of life changes from time to time and people requirements have changed and become so complicated recently with the exposure to advanced technology that has been attached with our daily life activities. A survey has been conducted among some Malaysian Government departments and agencies to elicit the main factors which participate in the success of projects and what the importance level of implementing an effective change management over projects that lead to sustainability and productivity of the organizations. This survey results have been received as a quantitative feedback that makes it clear to make a conclusion.